(untitled) (Jurnal Ipteks Terapan, 2023)
One way to maintain and improve the quality of service and security on the network of an institution of the West Pasaman Regency Archives and Library Office is to add a VPN feature. Administrators who are always monitoring traffic by accessing routers and access points to determine network conditions. There are times when the Administrator is on a public network, so he cannot access routers and access point devices because the public IP obtained is Dynamic (random). To overcome these problems, the Network Development Life Cycle (NDLC) method is carried out by combining the L2TP and IPSec VPN protocol systems that exist on Mikrotik. VPN is a private and secure network using a public network such as the internet. One of the security bases for VPN technology is Internet Protocol Security (IPSec). IPSec is a protocol used to secure datagram transmission on TCP/IP-based networks. This study aims to design and implement a Virtual Private Network (VPN) network system by utilizing a public network, where this system provides advanced security enhancements to internet networks using IPSec